Cutaneous Wound Healing: A Review about Innate Immune Response and Current Therapeutic Applications - Yara Adib; Armand Bensussan; Laurence Michel (Hindawi Limited, 2022)
Skin wounds and compromised wound healing are major concerns for the public. Although skin wound healing has been studied for decades, the molecular and cellular mechanisms behind the process are still not completely clear. The systemic responses to trauma involve the body's inflammatory and immunomodulatory cellular and humoral networks. Studies over the years provided essential insights into a complex and dynamic immunity during the cutaneous wound healing process. This review will focus on innate cell populations involved in the initial phase of this orchestrated process, including innate cells from both the skin and the immune system.